2011
DOI: 10.1590/s0103-50532011000400015
|View full text |Cite
|
Sign up to set email alerts
|

Nanoporous of W/WO3 Thin Film Electrode Grown by Electrochemical Anodization Applied in the Photoelectrocatalytic Oxidation of the Basic Red 51 used in Hair Dye

Abstract: Eletrodo nanoporoso auto-organizado de W/WO 3 pode ser obtido através da anodização eletroquímica de placas de W em solução de NaF 0,15 mol L -1 como eletrólito suporte, aplicando uma rampa de potencial de 0,2 V s -1 , até alcançar 60 V, mantendo por 2 h. A forma monoclínica altamente ordenada do WO 3 é majoritária quando calcinado a 450 0 C durante 30 min, obtendo uma maior fotoatividade quando irradiada na luz visível em relação a luz UV. O eletrodo promove a descoloração total do vermelho básico 51, utiliza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 45 publications
(65 reference statements)
1
9
0
Order By: Relevance
“…W 2 O 5 þ 2 H þ þ 2 e À ð4Þ Table 1 summarizes the various electrochemical approaches for the synthesis of nanostructured WO 3 thin films through anodization: even when using the electrochemical anodization method alone, different synthesis approaches can be adopted as evidenced by the various pretreatments, electrolytes, applied potentials, and annealing temperatures used. [23] Hahn et al reported the use of a threeelectrode electrochemical cell to prepare WO 3 in an electrolyte containing HClO 4 and NaClO 4 applying a potentials in the ranges from 10-100 V. [24] They concluded that the nanoporous WO 3 structure formed had a uniform surface with an average pore diameter of 40 nm and a pore length of 16 mm. For instance, Fraga et al prepared W/WO 3 thin films by anodization of W foil in a NaF solution by using a conventional two-electrode electrochemical cell.…”
Section: Electrochemical Anodizationmentioning
confidence: 99%
See 1 more Smart Citation
“…W 2 O 5 þ 2 H þ þ 2 e À ð4Þ Table 1 summarizes the various electrochemical approaches for the synthesis of nanostructured WO 3 thin films through anodization: even when using the electrochemical anodization method alone, different synthesis approaches can be adopted as evidenced by the various pretreatments, electrolytes, applied potentials, and annealing temperatures used. [23] Hahn et al reported the use of a threeelectrode electrochemical cell to prepare WO 3 in an electrolyte containing HClO 4 and NaClO 4 applying a potentials in the ranges from 10-100 V. [24] They concluded that the nanoporous WO 3 structure formed had a uniform surface with an average pore diameter of 40 nm and a pore length of 16 mm. For instance, Fraga et al prepared W/WO 3 thin films by anodization of W foil in a NaF solution by using a conventional two-electrode electrochemical cell.…”
Section: Electrochemical Anodizationmentioning
confidence: 99%
“…For instance, Fraga et al prepared W/WO 3 thin films by anodization of W foil in a NaF solution by using a conventional two-electrode electrochemical cell. [23] They found that the particle size of the nanoporous WO 3 layer formed was around 100 nm and that the thin film had a great uniformity. Moreover, the absorption of the thin films was extended to wavelengths above 480 nm (into the visible light spectrum) and thus, good photoactivity is achieved.…”
Section: Electrochemical Anodizationmentioning
confidence: 99%
“…After magnetron sputtering deposition, a two electrode system with a platinum cathode was used to anodize the W/Ti thin films in 0.3 M NH 4 F dissolved in ethylene glycol (98% anhydrous, Sigma Aldrich) to which 4 vol.% deionized water had been added. The voltage was ramped up to 10 V at a sweep rate of 0.1 V s −1 and then held for a period of 40 min (Keithley 236 Source Measuring Unit); the use of voltage ramp reduces solvent breakdown in the early stages of oxide growth that can occur if the maximum voltage is applied immediately.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, the nanoparticles are attractive for water purification since they are capable of removing biological contaminants, besides of simple chemicals. For instance, it is known that TiO 2 enhances antibacterial effect [2][3][4][5], whereas WO 3 can be efficiently used to eliminate organic pollutants [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%